Pressure Masks for Facial Scar Treatment after Oncological Reconstruction: Long-Term Patient Satisfaction and Quality of Life - De Henau, Melissa; van Kuijk, Sander M.J.; Colla, Carlo; Van den Kerckhove, Eric; Van der Hulst, Rene R.W.J.; Piatkowski, Andrzej (Facial Plastic Surgery, 2023)
Introduction With increasing incidence of facial skin cancer, more patients undergo facial reconstruction following Mohs micrographic surgery (MMS). Aesthetically unpleasing, thickened facial flaps, and disturbing scars can be treated with a pressure mask with inner silicone lining to help improve functional and aesthetic outcomes. However, data on long-term patient satisfaction and quality of life (QoL) following this treatment are lacking.Methods We aimed to assess long-term satisfaction and QoL of patients who underwent local flap reconstruction following MMS. Patients treated between January 2012 and October 2020 were invited to answer FACE-Q and SCAR-Q questionnaires. Demographic data, skin cancer type and location, type of reconstruction, postoperative complications, duration of pressure mask therapy, daily compliance, and additional scar treatment were collected to explore possible predictors.Results Of 92 eligible patients, 50 responded. Eighteen respondents were male (36%) and 32 were female (64%). Mean duration of pressure mask therapy was 10.20 ± 4.61 months. Patients were 61.14 ± 32.91 months after completion of pressure mask therapy upon participation. Patients whose reconstruction consisted of multiple flaps had significantly worse outcomes in social function (p = 0.012), scar appearance (p = 0.045), and scar symptoms (p = 0.008). A trend of increasing time since therapy completion predicting better outcomes was observed for all scales, and it was a significant predictor for better scar appearance (p = 0.001) and less scar symptoms (p = 0.001).Conclusion Pressure mask treatment for facial flaps and scars following MMS results in good long-term patient satisfaction and QoL. Multiple local flaps, reflecting a larger skin defect postexcision, is a predictor for worse outcomes in social function, scar appearance, and symptoms. Increasing time is associated with increasing satisfaction, which reflects satisfactory and stable long-term effects of treatment, possibly combined with more acceptance of the result over time.
Keywords: scars; facial pressure mask; pressure therapy; quality of life; patient-reported outcome